Pengaruh Variabel Makro Ekonomi Terhadap Ekspor Nonmigas Indonesia - yeni wati; Mike Triani; Reni Novianti Sari (Economac: Jurnal Ilmiah Ilmu Ekonomi, 2018)
Abstract This study aims to determine the effect of Inflation, National Income, Interest Rate and Money Supply through exchange rate moderation variables to non-oil and gas exports in Indonesia. The type of research used is descriptive and associative research. The type of data in this study is secondary data and time series data in the form of monthly and quarterly data from 2005 to 2016. Data analysis used is descriptive analysis and inductive analysis. In the inductive analysis there are several tests: Moderated Regression Analysis (MRA), classical assumption test and t test. This result shows that (1) exchange rate has no significant effect to moderate the relationship between inflation to non-oil and gas exports in Indonesia (2) Exchange rate has significant effect to moderate the relationship between national income to non-oil exports in Indonesia (3) Interest rate has no significant effect moderate relationship Interest rate on non-oil and gas exports in Indonesia (4) The exchange rate has a significant effect on moderating the relationship between the money supply to non-oil and gas exports in Indonesia.